THE CORRELATION BETWEEN WATCHING ENGLISH SUBTITLED MOVIES AND THE VOCABULARY MASTERY OF SECOND SEMESTER ENGLISH STUDY PROGRAM STUDENTS - Dwifani, Gita Rizkiya; Erni, Erni; Syarfi, M. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research aimed to determine whether there is any significantcorrelation between watching English-subtitled movies and the vocabulary mastery ofsecond-semester students of English Study Program FKIP Universitas Riau. Thisresearch used a correlational research design. The number of samples were 38 studentsof the second-semester English Study Program. This study used a probability samplingmethod. In conducting this research, the researcher used questionnaire to obtaininformation on the students’ activity of watching English-subtitled and vocabulary test(VLT) to find out students’ vocabulary mastery. The data were analyzed by using SPSS21 Version. The findings and results of the research showed that the correlation betweenwatching English-subtitled movies and their vocabulary mastery is very strong.Key Words: Correlation, Watching English-Subtitled Movies, Vocabulary Mastery